Esterase Inhibition Study in Different Tissues (Intestine, Muscle and Brain) of Fresh Water Cat Fish Heteropneustesfossilis through Polyacrylamide Gel Electrophoresis - BheemRao T.; Ganesh K.; Sanjeevaiah A (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Esterase polymorphism was studied in different tissues of stinging catfish (Heteropneustesfossilis) viz; intestine, muscle and brain. Intestine showed ER esterases(Esterases resistant to inhibitors) and CE esterases (Carboxylesterases), muscle showed ChE (Cholinesterases) and CHspesterases (Enzymes which were inhibited by Paraoxon, Eserine, and pCMB) and brain showed ChE(Cholinesterases) and Esdp(Esterases inhibited by Eserine alone) esterases. The present study was carried out to find out tissue specific esterase banding patterns in different tissues of H.fossilis. Electrophoretic banding patterns of esterase of different tissues showed species specific variation which could be successfully used for identification of fish species. Electrophoretic pattern of esterases of different tissues show species specific variation, it could be successfully used for the identification of fish species